Cleaning of Root Canal System by Different Irrigation Methods - Tanomaru-Filho, Mário; Miano, Lucas Martinati; Chávez-Andrade, Gisselle Moraima; Torres, Fernanda Ferrari Esteves; Leonardo, Renato de Toledo; Guerreiro-Tanomaru, Juliane Maria (Jaypee Brothers Medical Publishing, 2015)
OBJECTIVE: The aim of this study was to compare the cleaning of main and lateral canals using the irrigation methods: negative pressure irrigation (EndoVac system), passive ultrasonic irrigation (PUI) and manual irrigation (MI). MATERIALS AND METHODS: Resin teeth were used. After root canal preparation, four lateral canals were made at 2 and 7 mm from the apex. Root canals were filled with contrast solution and radiographed pre- and post-irrigation using digital radiographic system [radiovisiography (RVG)]. The irrigation protocols were: MI1-manual irrigation [22 G needle at 5 mm short of working length-WL]; MI2-manual irrigation (30G needle at 2 mm short of WL); PUI; EV1-EndoVac (microcannula at 1 mm short of WL); EV2-Endovac (microcannula at 3 mm short of WL). The obtained images, initial (filled with contrast solution) and final (after irrigation) were analyzed by using image tool 3.0 software. Statistical analysis was performed by analysis of variance (ANOVA) and Tukey tests (5% significance level). RESULTS: EV1 and EV2, followed by PUI showed better cleaning capacity than manual irrigation (MI1 and MI2) (p < 0.05). CONCLUSION: Negative pressure irrigation and PUI promoted better cleaning of main and simulated lateral canals. CLINICAL SIGNIFICANCE: Conventional manual irrigation technique may promote less root canal cleaning in the apical third. For this reason, the search for other irrigation protocols is important, and EndoVac and PUI are alternatives to contribute to irrigation effectiveness.
Keywords: Endodontics; Negative pressure irrigation; Passive ultrasonic irrigation; Root canal cleaning